Метод визначення потоків рекреантів за допомогою модифікованої ґравітаційної моделі на базі нечіткої логіки - Liakhov, S. A.; Vikliuk, Ya. I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2010)
A method for calculation of index territory attractivity on the basis of fuzzy logic is proposed. The modified gravitation model used for forecast of the number of potential recreants is improved by this method. Calculations based on the new model are performed, and a comparative analysis of the obtained results is presented.